Pengaruh Perceived Usefulness, Perceived Ease Of Use, Product Features Dan Reference Group Terhadap Keputusan Penggunaan Tik Tok - Dewi Noor Susanti; Rahma Wulandari (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This study aims to determine the effect of perceived usefulness, perceived ease of use, product features and reference groups on the decision to use TikTok users in Kebumen Regency. The population in this study are all users of the TikTok application in Kebumen Regency who have used and are currently using the TikTok application. This study used a purposive sampling method in taking samples with as many as 125 respondents. This research uses quantitative methods. Data analysis used multiple linear regression analysis with the SPSS 25 for windows program. Based on statistical methods, validity test, reliability test, multicollinearity test, heteroscedasticity test, normality test, multiple linear regression test, partial test, simultaneous test and coefficient of determination test were carried out. Based on the research results, it can be seen that perceived usefulness, perceived ease of use, product features and reference groups influence the decision to use by 50.1%. The results of this study indicate that based on the validity and reliability tests, all variables are declared valid and reliable. Based on the results of the t-test for perceived usefulness, perceived ease of use and product features each have a significant effect on the decision to use, while the reference group has no significant effect on the decision to use.